The study of redistribution in residual stresses during fatigue crack growth - Noghabi, Mohammad; I. Sattari-far; H. Hosseini Toudeshky (Journal of Mechanical Engineering and Sciences, 2021)
Numerical and experimental study was conducted on fatigue crack growth (FCG) of metallic components to investigate the redistribution of mechanical residual stresses during FCG. To this end, the compact tension specimens of an aluminium alloy were used. In addition, mechanical residual stresses were introduced near the crack tip by applying compressive and tensile loads, followed by visually observing the side-surface of the specimens to estimate the crack growth length. In the numerical simulation, cyclic J-integral was used as the crack growth fracture parameter and a good agreement was observed between the numerical and experimental results. The results of the finite element method demonstrated a clear redistribution of mechanical residual stresses during FCG. After a few cycles, the residual stress field around the crack tip reached a lower magnitude value confined in a smaller zone, although this zone was stable during the remaining fatigue process. Finally, present study evaluated the effect of stress ratio, load amplitude, and initial residual stresses level on the redistribution of residual stresses. It was observed that the residual stresses are mainly released during the first steps of fatigue loading.